Effectiveness of chest physiotherapy using passive slow expiratory techniques in dogs with airway fluid accumulation: A randomized controlled trial. (11th March 2021) - Pouzot‐Nevoret, Céline; Magnin, Mathieu; Barthélemy, Anthony; Goy‐Thollot, Isabelle; Cambournac, Maxime; Nectoux, Alexandra; Allaouchiche, Bernard
Abstract: Background: Prolonged slow expiration (PSE) and assisted cough (AC) are airway clearance techniques feasible and well tolerated in dogs. Objectives: To evaluate the effectiveness of PSE and AC as chest physiotherapy (CP) techniques in dogs with airway fluid accumulation. Animals: Thirty‐one client‐owned dogs hospitalized in an intensive care unit from October 2014 to May 2018. Methods: Prospective randomized controlled trial. Dogs presented with or developing acute dyspnea during hospitalization associated with airway fluid accumulation were assigned to CP group (medical treatment and CP, 15 dogs) or control group (medical treatment alone, 16 dogs). The arterial partial pressure of oxygen (PaO2 ) to fraction of inspired oxygen (FiO2 ) ratio (P/F ratio; PaO2 /FiO2 × 100) was calculated daily for the 1st 48 hours of hospitalization and using the last arterial blood gas performed before discharge or death. The ratio of days of hospitalization with oxygen/total number of hospitalization days (ratio of oxygen‐free‐days [O2 Free]) was calculated. Results: During the 1st 48 hours, the P/F ratio increased significantly in the CP group compared to the control group (+ 35.1 mm Hg/day; 95% confidence interval [CI] = 0.4‐57.5; P = .03). The (median; 1st quartile to 3rd quartile) difference between the P/F ratio at discharge and inclusion was significantly higher in the CP group (178 mm Hg; 123‐241) than in the control group (54 mm Hg; −19 ‐ 109; P = .001). Mean O2 Free increased by 46.4% in the CP group compared with control group (95% CI = 16‐59; P = .001). Mortality was 13% (2/15) in the CP group and 44% (7/16) in the control group ( P = .07). Conclusions and Clinical Importance: Prolonged slow expiration and AC improved P/F ratio within 48 hours and decreased need for oxygenation in dyspneic dogs with acute airway fluid accumulation.